Penerapan Narasi Ekspositoris pada Penulisan Naskah Film Dokumenter "Mindful Sip: Matcha Beyond the Trend" - Ranissa Azahra; Dian Wardiana Sjuchro; Kokom Komariah (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
Documentary film scriptwriting is a crucial element in structuring and delivering information coherently to audiences. This article examines the application of expository narrative in the scriptwriting of the documentary film Mindful Sip: Matcha Beyond the Trend, which addresses the social phenomenon of matcha consumption among Generation Z in Indonesia. The creative process was conducted through pre-production, production, and post-production stages, with scriptwriting as the primary focus. The narrative is structured through three sequences aligned with the three-act framework: sequence orientation introduces the matcha phenomenon contextually and factually; sequence development elaborates the issue across social, scientific, and personal dimensions; and Sequence resolution synthesizes the overall exposition while offering a non-judgmental space for audience reflection. The findings indicate that expository narrative, applied through these three sequences, enables coherent, communicative, and critically reflective scriptwriting. This approach demonstrates how documentary scriptwriting can function not merely as a textual framework, but as the primary instrument in constructing meaningful narratives about contemporary social phenomena.